THE EFFECT OF SELF-EFFICACY AND SCHOOL ENVIRONMENT ON INTEREST IN CONTINUING EDUCATION TO HIGHER EDUCATION IN SENIOR HIGH SCHOOL STUDENTS - Amilia, Aisah; Faslah, Roni; Yohana, Corry (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to determine the effect of self-efficacy and school environment on the interest in continuing education to higher education in high school students 1 Cawang Baru. This research was conducted for 7 months starting from January 2022 to July 2022. The method used in this study is a survey method. The sampling technique used was the saturated sample technique, so that the total population of the total population was obtained, namely the 12th grade students of Cawang Baru 1 Senior High School, totaling 73 respondents. Data was collected through distributing questionnaires using a Likert scale. Based on the results of the research conducted, it was found that self-efficacy has a positive and significant effect on the interest in continuing education to college. School environment has a positive and significant effect on interest in continuing education to college. Self-efficacy and school environment together have a positive and significant effect on students' interest in continuing their education to higher education. In accordance with the research hypothesis.